2014
DOI: 10.7314/apjcp.2014.15.7.3233
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Analysis of Prognostic Factors in Male Breast Cancer in Serbia

Abstract: Background: The aim of this study was to analyze the demographic and clinical characteristics of male breast cancer patients in Serbia, and furthermore to determine overall survival and predictive factors for prognosis. Materials and Methods: In the period of 1996-2006 histopathological diagnosis of breast cancer was made in 84 males at the Institute for Oncology and Radiology of Serbia. For statistical analyses the Kaplan-Meier method, long-rank test and Cox proportional hazards regression model were used. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 45 publications
(32 reference statements)
1
13
0
Order By: Relevance
“…Six cases had distant metastasis. Nipple involvement was noted in 9 cases, of which 7 located in central quadrant, 8 were IDC, 1 was pure DCIS and 1 had in situ component in addition to invasive component. Tumor necrosis was seen in 9 cases (27.3%), perineural invasion in 15 cases (45,5%), tumor emboli in dermal lymphatics in 10 cases (30.3%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six cases had distant metastasis. Nipple involvement was noted in 9 cases, of which 7 located in central quadrant, 8 were IDC, 1 was pure DCIS and 1 had in situ component in addition to invasive component. Tumor necrosis was seen in 9 cases (27.3%), perineural invasion in 15 cases (45,5%), tumor emboli in dermal lymphatics in 10 cases (30.3%).…”
Section: Resultsmentioning
confidence: 99%
“…Grujicic et al and Bruce et al reported IDC as most common subtype because male breast normally consist of only ducts [8,9]. Lobular tissue is present only in case of increased estrogen exposure [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Breast cancer remains a significant problem for global health as it is one of the most common cause of tumorrelated death world-wide (Fouz et al, 2013;Engin et al, 2013;Sedighi et al, 2013;Zhu et al, 2013;Wu et al , 2014;Cabuk et al, 2014;Chin et al, 2014;Fouladi et al, 2014;Majeed et al, 2014;Gogia et al, 2014;Liu et al, 2014;Louisa et al, 2014;Moazzezy et al, 2014;Niu et al, 2014;Rizalar et al, 2014;Sipetic-Grujicic et al, 2014;Prajoko et al, 2014;Inanc et al, 2014;Varol et al, 2014;Yadav et al, 2014). Pemetrexed is a novel multitargeted antifolate that inhibits several enzymes in the de novo pathways of pyrimidine and purine biosynthesis, including thymidylate synthase, dihydrofolate reductase, and glycinamide ribonucleotide ormyltransferase.…”
Section: Discussionmentioning
confidence: 99%